Mirando fotografías, pensando en arquitectura - Campbell, Hugh (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
This article offers some reflections on the relationship between architecture and photography based on the outcomes of a graduate seminar, ‘Space Framed’, which asks students to engage critically with photographic projects dealing with aspects of the built and inhabited world. The seminar aims to move beyond the typical terms of the photography-architecture relationship, in which, on the one hand, architecture is seen as being ‘served’ by photography amd, on the other hand, architecture serves merely as the subject matter for photography. Instead, the focus is on the shared impulses and modes of the two disciplines: the study of how space is shaped, framed and inhabited. The article concludes with two case studies which are representative of two ‘tendencies’ within photography – the first concerning itself with fleeting moments of wonder, the second describing the larger social scene. The Japanese photographer Rinko Kawauchi exemplifies the first tendency, and the American Alec Soth the second. Reflections are offered on what this study can offer to developing teaching and research in this area.